Aramaic sources of Mark's Gospel - Casey, Maurice (Society for New Testament Studies monograph series, 1998)
This 1999 book was the first to use all the Aramaic Dead Sea Scrolls to reconstruct original Aramaic sources from parts of Mark's Gospel. The scrolls enabled the author to revolutionize the methodology of such work, and to reconstruct whole passages which he interpreted in their original cultural context. The passages from which sources are reconstructed are Mark 9.11-13; 2.23-3.6; 10.35-45; and 14.12-26. A detailed discussion of each passage is offered, demonstrating that these sources are completely accurate accounts from the ministry of Jesus, from early sabbath disputes to his final Passover. An account of the translation process is given, showing how problems in Mark's text arose from the difficulty of translating some Aramaic expressions into Greek, including the notoriously difficult 'son of man'. A very early date for these sources is proposed, implying a date of c. 40 CE for Mark's Gospel.